2010
DOI: 10.1080/14763141.2010.511679
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of player-surface interaction on artificial soccer turf

Abstract: The purpose of this study was to evaluate the traction characteristics of four different stud configurations on Fédération Internationale de Football Association (FIFA) 2-Star, third-generation artificial soccer turf. The investigated stud configurations were hard ground design, firm ground design, soft ground design, and an experimental prototype. The concept of this study combines performance, perception, biomechanical, and mechanical testing procedures. Twenty-five soccer players took part in the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 15 publications
0
49
1
Order By: Relevance
“…It is believed that differences in these playing surfaces require different footwear characteristics for optimising performance. Performance results comparing shoe-surface interactions in soccer are normally focused on the type of turf surface or outsole cleat design (Gains et al 2010, M€ uller et al 2010, Sterzing et al 2010. When comparing natural grass to artificial turf, some studies have shown an increase in athletic performance on artificial turf (Gains et al 2010, while other studies have shown no differences between the two surfaces (Ford et al 2006).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…It is believed that differences in these playing surfaces require different footwear characteristics for optimising performance. Performance results comparing shoe-surface interactions in soccer are normally focused on the type of turf surface or outsole cleat design (Gains et al 2010, M€ uller et al 2010, Sterzing et al 2010. When comparing natural grass to artificial turf, some studies have shown an increase in athletic performance on artificial turf (Gains et al 2010, while other studies have shown no differences between the two surfaces (Ford et al 2006).…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…In recent years a lot of research has focused on the effects of different cleat designs on the human body especially on lower extremities The aim of these studies was to compare different stud configurations to find out which cleat shape and arrangement stresses the body least and/or to analyse different soccer specific movements that bear a high risk for injuries (Smith et al 2002, Eils 2004, Smith et al 2004, Gehring et al 2007, Kaila 2007, Orendurff 2007, Wong et al 2007, M€ uller et al 2010b, Stefanyshyn et al 2010, Bentley et al 2011. Less attention was paid to the performance increasing aspects of soccer shoes, although there is evidence that shoe construction can affect kicking accuracy, kicking velocity, running speed or ball handling significantly (Sterzing and Hennig 2008, Sterzing et al 2009, M€ uller et al 2010a, Sterzing et al 2011, Smith 2012, Hennig and Althoff 2013. Even less research has focused on gender-specific soccer footwear, although the number of female soccer players has considerably grown during recent years.…”
Section: Introductionmentioning
confidence: 98%
“…These phenomena may be induced by the geometry of the blades, which are supposed to prevent rotation of the foot to increase performance in sidestep and cutting maneuvers. Studies conducted with professional soccer players performing different motions and maneuvers by employing motion analysis and inverse dynamics models (Gehring, Rott, Stapelfeldt, & Gollhofer, 2007;Kaila, 2007) showed that studded and bladed cleats had no effect on the loads acting in the knee but influenced the player performance and perception to some degree (Mü ller Sterzing, Lange, & Milani, 2010). Direct measurements and comparisons of the rotational resistance of the different types of cleats are currently available (Andréasson, Lindenberger, Renströ m, & Peterson, 1986;Cawley, Heidt, Scranton, Losse, & Howard, 2003;Grund & Senner, 2010;Heidt et al, 1996;Torg & Quedenfeld, 1971;Villwock, Meyer, Powell, Fouty, & Haut, 2009), but these studies neither support nor reject the hypothesis that the cleat design has an influence on the stresses in the knee joint.…”
Section: Introductionmentioning
confidence: 99%